Association of Fluid Overload with Escalation of Respiratory Support and Endotracheal Intubation in Acute Bronchiolitis Patients - Baloglu, Orkun; Flagg, Lauren K.; Suleiman, Ahmad; Gupta, Vedant; Fast, Jamie A.; Wang, Lu; Worley, Sarah; Agarwal, Hemant S. (Journal of Pediatric Intensive Care, 2021)
Fluid overload has been associated with increased oxygen requirement, prolonged duration of mechanical ventilation, and longer length of hospital stay in children hospitalized with pulmonary diseases. Critically ill infants with bronchiolitis admitted to the pediatric intensive care unit (PICU) also tend to develop fluid overload and there is limited information of its role on noninvasive respiratory support. Thus, our primary objective was to study the association of fluid overload in patients with bronchiolitis admitted to the PICU with respiratory support escalation (RSE) and need for endotracheal intubation (ETI). Infants ≤24 months of age with bronchiolitis and admitted to the PICU between 9/2009 and 6/2015 were retrospectively studied. Demographic variables, clinical characteristics including type of respiratory support and need for ETI were evaluated. Fluid overload as assessed by net fluid intake and output (net fluid balance), cumulative fluid balance (CFB) (mL/kg), and percentage fluid overload (FO%), was compared between patients requiring and not requiring RSE and among patients requiring ETI and not requiring ETI at 0 (PICU admission), 12, 24, 36, 48, 72, 96, and 120 hours. One-hundred sixty four of 283 patients with bronchiolitis admitted to the PICU qualified for our study. Thirty-four of 164 (21%) patients required escalation of respiratory support within 5 days of PICU admission and of these 34 patients, 11 patients required ETI. Univariate analysis by Kruskal-Wallis test of fluid overload as assessed by net fluid balance, CFB, and FO% between 34 patients requiring and 130 patients not requiring RSE and among 11 patients requiring ETI and 153 patients not requiring ETI, at 0, 12, 24, 36, 48, 72, 96 and 120 hours did not reveal any significant difference (p >0.05) at any time interval. Multivariable logistic regression analysis revealed higher PRISM score (odds ratio [OR]: 4.95, 95% confidence interval [95% CI]: 1.79–13.66; p = 0.002), longer hours on high flow nasal cannula (OR: 4.86, 95% CI: 1.68–14.03; p = 0.003) and longer hours on noninvasive ventilation (OR: 11.16, 95% CI: 3.36–36.98; p < 0.001) were associated with RSE. Fluid overload as assessed by net fluid balance, CFB, and FO% was not associated with RSE or need for ETI in critically ill bronchiolitis patients admitted to the PICU. Further prospective studies involving larger number of patients with bronchiolitis are needed to corroborate our findings.
Keywords: bronchiolitis; fluid overload; endotracheal intubation; respiratory support; pediatric intensive care unit